Personal relationships and institutional framework conditions. Socialization aspects of identity development today: Relações pessoais e condições estruturais institucionais: aspectos de socialização do desenvolvimento da identidade hoje - Axel Foeller-Mamcini (Revista Trama Interdisciplinar, 2025)
Personal relationships and institutional framework conditions. Socialization aspects of identity development today